National sports and competitions in applied physical education of schoolchildren of the Sakha Republic: theoretical aspect - Efimov A.A. ,; Ponomarev V.V. ,; Prikhodov D.S. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to theoretically substantiate and develop the program content of applied physical education for schoolchildren of the Sakha Republic based on national sports and competitions and recommend it for practice. Methods and structure of the study. The study was conducted during 2024 in schools of the Sakha Republic. The program and methodological support of applied physical education of schoolchildren was analyzed, pedagogical observations, conversations, questionnaires were conducted, the accumulated factual material was systematized, applied skills and abilities of household, hunting, fishing and other economic activities for productive life in local climatic and geographical conditions of residence were tested. Results and conclusions. An analytical review of scientific and methodological literature on the subject of the work, pedagogical observations of practical classes, conversations, and software analysis showed that insufficient attention is paid to applied physical education in the schools of the Sakha Republic, training the younger generation for effective and productive economic, social, and everyday activities in difficult climatic, geographical, and natural conditions of life in the Sakha Republic. Based on the collected and systematized factual material, a variable program of applied physical education of schoolchildren of the Sakha Republic was developed, which includes the following sections: national sports of the Sakha Republic; applied exercises that form economic skills for traditional Yakut life; national exercises that form applied hunting and fishing skills; applied survival skills in the taiga and traditional forms of hardening the body from low temperatures. A correctly formed program of applied physical education of schoolchildren of Yakutia contributes to the formation of economic and everyday readiness of the younger generation for effective activity and living in the harsh natural and climatic conditions of the Sakha Republic.